2003
DOI: 10.1021/ol0340179
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electronic Effects in the Asymmetric Heck Reaction with the BIPI Ligands

Abstract: [structure: see text] The new BIPI ligands are phosphinoimidazolines that can be electronically tuned in three different ligand regions to explore electronic effects in asymmetric catalysis. Their application to the asymmetric Heck reaction (AHR) in the creation of a chiral quaternary center is described. Enantioselectivity is shown for the first time to depend linearly on phosphine electron density. Changing the ligand basicity by variation of the R(2) or R(3) substituents reverses facial selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(46 citation statements)
references
References 11 publications
0
44
0
Order By: Relevance
“…It was found that O-ethyl 2-fl uorobenzimidate tetrafl uoroborate salt 11, a reagent introduced recently by Busacca et al for the synthesis of phosphinoimidazoline ligands, 26 provides an excellent nucleus for the assembly of a focused array of PHOX ligands. The approach taken is illustrated in Scheme 1, and involves initial condensation of a chiral amino alcohol with 11, followed by introduction of the desired diarylphosphino group by nucleophilic aromatic substitution upon the resulting (2-fl uoro)aryloxazoline.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that O-ethyl 2-fl uorobenzimidate tetrafl uoroborate salt 11, a reagent introduced recently by Busacca et al for the synthesis of phosphinoimidazoline ligands, 26 provides an excellent nucleus for the assembly of a focused array of PHOX ligands. The approach taken is illustrated in Scheme 1, and involves initial condensation of a chiral amino alcohol with 11, followed by introduction of the desired diarylphosphino group by nucleophilic aromatic substitution upon the resulting (2-fl uoro)aryloxazoline.…”
Section: Resultsmentioning
confidence: 99%
“…[4] However, they have never been used in Pd-catalyzed asymmetric allylic substitution reactions, a domain where PHOX ligands are one of the most important players. [1d,5] We wish to report in the present paper the structural optimization of modular PHIM ligands using the Pd-catalyzed asymmetric allylic substitution reaction as a benchmark.…”
mentioning
confidence: 99%
“…Thus, ligands 11 and 12 were prepared through CuAAC reactions [9] from N-propargylic derivatives 13 and 14 (Scheme 1). The triazole moieties were installed by reaction with benzyl bromide in the presence of sodium azide, l-ascorbic acid and catalytic amounts of CuSO 4 , and the phosphino units were introduced in [b] By NMR. [c] By HPLC on a chiral stationary phase.…”
mentioning
confidence: 99%
“…Among the many PHOX analogues that we tested, readily available phosphinites of type 12 and 13 proved to be the most versatile ligands. Subsequently, we added phosphinoimidazolines, such as type 14, to our collection of ligands (32,33), as well as pyridine-and quinoline-derived P,N-ligands of type 15 and 16 (34), all of which gave very promising results. Recently, other research groups have become interested in this class of catalysts and have reported additional variants of Ir complexes with P,N-ligands (35)(36)(37)(38)(39)(40) and, as a further modification, oxazoline ligands with a heterocyclic carbene unit instead of a phosphino group (41).…”
Section: Figmentioning
confidence: 99%